Media BISA (Bencana: Informasi, Solusi, Aksi) Upaya Meningkatkan Hardskill dan Softskill Mahasiswa Pendidikan Biologi Universitas Negeri Medan dalam Menghadapi Bencana Alam - Ummu Hanniyah; Finga Fitri Amanda; Sanimah Sanimah; Friends Silaban (Jurnal Tematik, 2026)
Indonesia is highly vulnerable to natural disasters, creating an urgent need for disaster preparedness education to enhance students’ competencies in responding to disaster situations. This study aimed to develop BISA Media (Disaster: Information, Solutions, and Action) and examine its effectiveness in improving the hard skills and soft skills of Biology Education students at Universitas Negeri Medan in dealing with natural disasters. The study employed a Research and Development approach based on a modified Borg and Gall model consisting of needs analysis, prototype design, expert validation, product revision, limited trial, and final revision. The developed product was an educational video integrating disaster information, biology-based solutions, and action-oriented disaster response simulations. The results revealed that BISA Media achieved a very high validity level, with an average validation score of 3.73 (93.3%) and an Aiken’s V value of 0.91. The implementation of the media significantly improved students’ hard skills, as indicated by an increase in mean scores from 61.25 on the pretest to 86.70 on the posttest, with an N-Gain score of 0.76 (high category). Students’ soft skills also improved from 70.6% to 88.4%, with an N-Gain score of 0.72 (high category). Positive user responses reached 93%, indicating high acceptance of the media. Therefore, BISA Media is feasible and effective for enhancing disaster preparedness competencies among Biology Education students. Future studies are recommended to develop more interactive digital features and implement the media on a broader scale. Keywords: BISA Media; disaster preparedness; hard skills; soft skills; biology education; disaster mitigation.